INFLUENCE OF TWO BIO-STIMULANTS IN AGRICULTURAL BEHAVIOR IN TOBACCO CROP (Nicotiana tabacum L.) - Calero, Alexander [UNESP] (2019)
With the objective of to evaluate the effect of two biostimulants on the agricultural behavior of the black tobacco crop ‘Sancti Spíritus 2006’ was developed an experiment in the collective framer “Sindulfo García”, Sancti Spíritus, Cuba, from october to december 2015. The following treatments were evaluated: control, inoculation and foliar application of ME-50 at 100 mg L−1, foliar application of Biobras-16™ at 0.05 mg L−1 and the combination of both. The main observations corresponded to the following morpho-agronomic variables: distance between nodes (cm), length and width of central leaves (cm), height of plants (cm) and the number of leaves per plant. The results showed that the application of the biostimulants ME-50, Biobras-16™, as well as their combination increased the morphological variables in the variety of black tobacco ‘Sancti Spíritus 2006’. The highest results were obtained with the combined application of the two biostimulants because they achieved the indicators observed compared with the individual use of ME-50 and BB-16 and increased the number of leaves per plant in relation to the control treatment in 35.51% at 64 ddt.